2016
DOI: 10.1007/s10903-015-0269-y
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Maternal Stress and the Risk of Lifetime Wheeze in Young Offspring: An Examination by Stressor and Maternal Ethnicity

Abstract: Background Prenatal psychosocial stressors may increase the risk of wheeze in young offspring; yet little attention has been given to the effects that maternal ethnicity may have on this relationship. Methods From a population-based cohort of 1,193 children, we assessed the effect of maternal prenatal stressors on the risk of lifetime wheeze in young offspring. We further studied whether maternal Latina ethnicity modified these associations. Results The risk of wheeze in the offspring was increased from hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…No experimental studies were found; therefore only analytical epidemiological studies were included, which comprised of 27 cohort studies, two case-control studies, and one cross-sectional study. The type of psychosocial stress indicators investigated in the studies included anxiety, [21][22][23][24]27,30,35,36,48,49 depression, [22][23][24]30,35,37,41,42 bereavemet, 29,32,38 work-related stress, 33,36,47,48 and NLEs, 19,20,25,26,28,31,34,39,40,[43][44][45][46]49,50 which were usually comprised of a composite of different indicators of stressors. Most studies assessed maternal stress using self-completed validated questionnaire; in a few studies maternal stress was assessed from population registers, particularly stress resulting from bereavement of a family member.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…No experimental studies were found; therefore only analytical epidemiological studies were included, which comprised of 27 cohort studies, two case-control studies, and one cross-sectional study. The type of psychosocial stress indicators investigated in the studies included anxiety, [21][22][23][24]27,30,35,36,48,49 depression, [22][23][24]30,35,37,41,42 bereavemet, 29,32,38 work-related stress, 33,36,47,48 and NLEs, 19,20,25,26,28,31,34,39,40,[43][44][45][46]49,50 which were usually comprised of a composite of different indicators of stressors. Most studies assessed maternal stress using self-completed validated questionnaire; in a few studies maternal stress was assessed from population registers, particularly stress resulting from bereavement of a family member.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most studies assessed maternal stress using self-completed validated questionnaire; in a few studies maternal stress was assessed from population registers, particularly stress resulting from bereavement of a family member. Twelve studies assessed the impact of maternal stress on asthma, 20,[27][28][29][30][31][32]34,37,38,42,46 eight studies on atopic eczema/dermatitis, [22][23][24]28,31,44,47,48 ten studies on wheeze, 20,[24][25][26][27][28]30,35,42,43,46 three studies on allergic rhinitis, 24,28,31 three on atopic sensitization, 27,31,42 and six studies on cord blood IgE or cytokines 19,21,36,39,45,50 (Table S1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Prenatal stress may impact the hypothalamic-pituitary axis (4), and hence, may lead to dysregulation of immune system function (5)(6)(7). Most published studies suggested that prenatal exposure to life stressors was associated with increased risk of asthma (8)(9)(10)(11)(12)(13)(14), whereas other studies reported no association (15,16). Moreover, inconsistencies exist regarding the strength of the association, prob-ably due to differences in the type of stress indicators, asthma measurement (prevalence versus incidence), and the inclusion of children at different ages.…”
mentioning
confidence: 99%
“…Asthma is not a single disease entity but encompasses several phenotypes, such as early-onset transient, early-onset persistent, and late-onset asthma (17). So far, most published studies addressed private life stressors (8)(9)(10)(11)(12)(13)(14)(15)(16), and the relative importance of work-related psychosocial factors during pregnancy on offspring asthma is not well understood. Only one study extended the focus to maternal self-reported job strain and the association to parent-reported asthma with an inherent risk of reporting bias (18).…”
mentioning
confidence: 99%
“…Maternal bereavement involving a spouse or child, one of the most extreme traumas a person may face, was found to be significantly associated with later allergic diseases,71617 and the number of stressful life events during pregnancy was also reported to show a dose-response relationship 6. Recently, studies using validated self-reported questionnaires have also been published 3581314181921. However, there are as yet no studies that applied observational or objective measures to assess maternal psychological status.…”
Section: Evidence Of the Impact Of Prenatal Maternal Distress On Allementioning
confidence: 99%